Biopolitical Education: The Edukators and the Politics of the Immanent Outside - Roland Vegso; Marco Abel (Studies in 20th & 21st Century Literature, 2016)
The article examines the relationship of biopower and cinema through the analysis of a specific film, Hans Weingartner’s The Edukators (2004). It argues that in the age of biopower, resistance to power cannot be conceived of in terms of a radical outside to power. Rather, biopolitical resistance must take place on the terrain of this power itself, that is, within the field of life. Therefore, what we call the “viral” politics of The Edukators must be interpreted precisely in this context. The film argues that the exhaustion of political paradigms inherited from the past century forces us to take the logic of biopower seriously. It presents a dual critique of the neoliberal exploitation of life and the politics of death that defines contemporary terrorism. In place of these two, it offers the audience the model of a certain “biopolitical education” that imagines resistance as fully immanent to the field of power.
Keywords: biopower; biopolitics; terrorism; realism; distribution of sensible; resistance; neoliberalism; German; cinema; The Edukators